Rekalibrasi Strategi Pertahanan Amerika Serikat 2026 - Kenzy Arta Fadillah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The increasingly complex geopolitical developments are feared to give rise to various threats to a country, so there is a need for a form of anticipation of these threats through the implementation of certain strategic patterns in anticipating threats to a country. The United States recently occurred after the release of the 2026 National Defense Strategy released by the Donald Trump administration on January 23, 2026. The US National Defense Strategy outlined 4 main pillars and was implemented in Venezuela, precisely on January 3 as a demonstration of strength at the beginning of the year. This article aims to understand the concept and strategy of the United States defense that has been updated in 2026. The main findings of this study show that the United States has taken various strategic steps in response to global geopolitical changes. With several important strategies involving not only the American military itself, but also the military and industrial allies both in the western region and the Indo-Pacific which are basically under pressure under the policies of the United States.